Persistence of immune responses to the HPV‐16/18 AS04‐adjuvanted vaccine in women aged 15–55 years and first‐time modelling of antibody responses in mature women: results from an open‐label 6–year follow‐up study. (11th September 2014) - Schwarz, T; Spaczynski, M; Kaufmann, A; Wysocki, J; Gałaj, A; Schulze, K; Suryakiran, P; Thomas, F; Descamps, D
<x xml:space="preserve">Abstract</x> Objective Evaluation of the long‐term HPV‐16/18 AS04‐adjuvanted vaccine immunogenicity persistence in women. Design Multicentre, open‐label, long‐term follow‐up (NCT00947115) of a primary phase–III study (NCT00196937). Setting Six centres in Germany and Poland. Population 488 healthy women (aged 15–55 years, age‐stratified into groups: 15–25, 26–45, and 46–55 years) who received three vaccine doses in the primary study. Methods Immune responses were evaluated in serum and cervicovaginal secretion (CVS) samples 6 years after dose 1. Anti‐HPV‐16/18 geometric mean titres (GMTs) were measured by enzyme‐linked immunosorbent assay (ELISA), and were used to fit the modified power‐law and piecewise models, predicting long‐term immunogenicity. Serious adverse events (SAEs) were recorded. Main outcome measures Anti‐HPV‐16/18 seropositivity rates and GMTs 6 years after dose 1. Results At 6 years after dose 1, all women were seropositive for anti‐HPV–16 and ≥97% were seropositive for anti‐HPV–18 antibodies. GMTs ranged from 277.7 to 1344.6 EU/ml, and from 97.6 to 438.2 EU/ml, for anti‐HPV–16 and anti‐HPV–18, respectively. In all age groups, GMTs were higher (anti‐HPV–16, 9.3–45.1‐fold; anti‐HPV–18, 4.3–19.4‐fold) than levels associated with natural infection (29.8 EU/ml). A strong correlation between serum and CVS anti‐HPV‐16/18 levels was observed, with correlation coefficients of 0.81–0.96 (anti‐HPV–16) and 0.69–0.84 (anti‐HPV–18). Exploratory modelling based on the 6–year data predicted vaccine‐induced anti‐HPV‐16/18 levels above natural infection levels for at least 20 years, except for anti‐HPV–18 in the older age group (piecewise model). One vaccine‐related and two fatal SAEs were reported. Conclusions At 6 years after vaccination, immune responses induced by the HPV‐16/18 AS04‐adjuvanted vaccine were sustained in all age groups.